Indian folklore - Goswāmī, Māmaṇi Raẏachama; Pattanaik, Prakash; Khāonda, Malaẏā (B.R. Pub. Corp. in collaboration with Assam Sahitya Sabha, Delhi Branch ; Distributed by BRPC (India), 2001)
Contributed articles presented at a National Seminar on Indian Folklore (1-3 February, 1998), Delhi.